Game-Changer: Unlocking Student-Athlete Success with Sleep and Later School Start Times - Fong-Isariyawongse, Joanna (Journal of Sports Medicine and Therapy, 2024)
This editorial explores the crucial yet often overlooked role of sleep in enhancing student-athlete performance and well-being. It highlights sleep’s impact on physical recovery, cognitive function, and emotional stability, emphasizing the unique benefits for athletes. The editorial examines the detrimental effects of early school start times on adolescent sleep patterns and their subsequent impact on academic and athletic performance. By advocating for policy changes that prioritize sleep, such as delaying school start times, this editorial presents a novel approach to optimizing student-athlete success. Through a synthesis of current research and practical insights, it urges stakeholders in education and sports to recognize and act upon the foundational importance of sleep, positioning it as a key component of athletic and academic excellence.